Answer:
The following polynomial can be factorized as,
f(x) =
![(x-4)(x-3)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3np175v6dnlv53d3i5wxf81vus3him5w9z.png)
Explanation:
It is given that at x = -2, the value of polynomial is zero, thus, by factor theorm,
(x+2) is the factor of the above polynomial.
By dividing the given polynomial by (x+2), we get,
F(x) =
![(x-4)(x^(2) -7x +12)](https://img.qammunity.org/2020/formulas/mathematics/high-school/6eaed8ay42zraare86eirordvewsrzcb4w.png)
This can be further simplified as,
=
![(x^(2) -4x-3x+12)](https://img.qammunity.org/2020/formulas/mathematics/high-school/q79z9nf5tab57chw6tr5id1d6zv0ylm9ce.png)
=
=
![(x-3)(x-4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/z7f2e8az55xi9z12s1cg39200wi4dipio2.png)
Thus the polynomial becomes,
f(x) =
![(x-4)(x-3)(x+2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/3np175v6dnlv53d3i5wxf81vus3him5w9z.png)